2011
DOI: 10.1093/ejo/cjr006
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional longitudinal assessment of facial symmetry in adolescents

Abstract: Recent advances in laser scanning technology provide the opportunity to examine faces in three dimensions. The aim of this prospective clinical study was to explore facial symmetry in healthy growing individuals and determine whether asymmetric changes occur during adolescent growth. Non-invasive laser surface scanning was performed to capture facial images of 60 Caucasian Finnish adolescents (30 males and 30 females, mean 11.5 years). Facial symmetry was analysed on images obtained at the initial scanning (T₁… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 26 publications
3
61
0
Order By: Relevance
“…This is in accordance with previous studies that report a greater facial asymmetry in subjects with unilateral functional CB, particularly in the lower part of the face. 3 Previous studies have shown that sex and age do not affect facial asymmetry, 22,29 which is in accordance with the results of the present study. Furthermore, no significant differences were seen in the facial parameters within each group (CB and no CB) according to different dentition phases for the upper and lower facial parts.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous studies that report a greater facial asymmetry in subjects with unilateral functional CB, particularly in the lower part of the face. 3 Previous studies have shown that sex and age do not affect facial asymmetry, 22,29 which is in accordance with the results of the present study. Furthermore, no significant differences were seen in the facial parameters within each group (CB and no CB) according to different dentition phases for the upper and lower facial parts.…”
Section: Discussionsupporting
confidence: 93%
“…6,7,23,24 Interestingly, our study used stimuli that varied the symmetry of the whole face from 50% less symmetric than the true face to perfect symmetry. Accordingly, the stimuli we used provide a reasonable representation of the range of asymmetry encountered in clinical practice, and our data give further insight to the nature of face symmetry judgment by both clinicians and laypersons.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly being reported in the literature that 3D facial scanners can be used in oral clinic, with the 3D facial models acquired by scanners being used for 3D quantitative diagnostic and treatment evaluation [4,5,6,7,8,9,10]. The accuracy of facial scanners in oral and maxillofacial clinical practice is a major focus of current research [11,12,13].…”
Section: Introductionmentioning
confidence: 99%